Penerapan Dan Efektifitas Senam Dismenore (Menstruasi) Terhadap Antisipasi Munculnya Nyeri Haid Pada Remaja Putri Di SMP Negeri Kota Bogor - Dwi Pratiwi Kasmara; Revie Fitria Nasution; Zumrotul Ula; Pratiwi Bayuningrum; Rahmaniyah R; Halimatussakdiyah Lubis (Journal on Education, 2025)
Menstruation is a physiological change in a woman's body that occurs periodically and is influenced by reproductive hormones, this usually occurs every month between adolescence and menopause. The purpose of the study was to determine changes in the pain scale in adolescent girls who experience dysmenorrhea before and after the implementation of dysmenorrhea exercises. This research method uses a descriptive case study by observing female adolescent respondents at SMP Negeri Kota Bogor who were given the implementation of dysmenorrhea exercises which were carried out for 3 meetings in 1 week with a time of ± 30 minutes each meeting. The results showed that after the implementation of dysmenorrhea exercises there was a decrease in the pain scale, before the gymnastics the pain scale was in the moderate pain category, after the dysmenorrhea exercises were carried out it was included in the mild pain category. The conclusion of the study stated that this dysmenorrhea exercise can reduce the pain scale in adolescent girls who experience dysmenorrhea.